Urip iku urup (life is lit) by service to others: a qualitative study of frontline healthcare workers' lived experiences providing patient care in Indonesia's COVID-19-designated hospital - Ayu Puspita Ningrum; Malene Missel (BMC, 2023)
Abstract Background While COVID-19 affects every walk of human life, it especially implicates healthcare workers at the forefront of the pandemic due to their vulnerable involvement in providing first-line treatment. This study presents the lived experiences of frontline healthcare workers serving in Indonesia's COVID-19-designated hospital, one of the severely afflicted healthcare settings wherein resource challenges, public health crisis, and political constraints intersect as policy conundrums. Methods Using a qualitative exploratory-descriptive approach, this study drew on thirteen in-depth, semi-structured interviews with frontline healthcare workers who have experiences providing first-line COVID-19 patient care in the COVID-19 hospital. The data analysis commenced with the verbatim transcription of the interview data, which was then subjected to a systematic thematic analysis employing hermeneutic phenomenological principles. Results The exploration of the participants' accounts reveals eight interconnected themes: facing resource scarcity and resignation; experiencing service-induced burnout due to occupational workload; encountering fears of being infected and infecting others; engaging in positivity through social connectedness; having dilemmas over healthcare rationing; developing negative emotions during patient interactions; coping through spirituality and religiosity; and embodying a life of service. Conclusion Managing healthcare in resource-limited, crisis settings presents multifaceted challenges that exceed mere structural modifications, requiring prioritized public health investment to ensure optimal patient care. Therefore, healthcare policy development and implementation should equally emphasize the well-being of frontline healthcare workers to foster sustainable healthcare delivery and achieve improved patient outcomes.